Adsorption-based cationic dyes using the carbon active sugarcane bagasse - Farahani, Meysam; Sheikh Abdullah, Siti Rozaimah; Hosseini, Soraya; Shojaeipour, Shahed (Elsevier, 2011)
The use of activated carbon made of sugarcane bagasse, to eliminate cationic dyes present in waste water was studied in this research. It investigates the potential use of activated carbon made of sugarcane bagasse. Increase in the PH of the dye solution caused an equivalent increment in its adsorption efficiency. This study demonstrates that activated carbon made from sugarcane bagasse is an efficient and cheap adsorbing agent and very effective at removing dyes present in solutions and the possibility of using it for a simple and inexpensive method of dye removal from waste waters in either stirred tank reactors or in batch reactors. The data obtained could be utilised to design an optimally productive system that uses either stirred tank reactors or batch reactors remove of cationic dyes from effluents industrial. This study predicts effect of activated carbon made from sugarcane bagasse on adsorption of cationic dyes.